The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/15476286.2017.1308998
|View full text |Cite
|
Sign up to set email alerts
|

A close-up view of codon selection in eukaryotic initiation

Abstract: When given an option to choose among a set of alternatives and only one selection is right, one might stop and reflect over which one is best. However, the ribosome has no time to stop and make such reflections, proteins need to be produced and very fast. Eukaryotic translation initiation is an example of such a conundrum. Here, scanning for the correct codon match must be fast, efficient and accurate. We highlight our recent computational findings, which show how the initiation machinery manages to recognize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Although at first glance, such issues may not seem important for the interpretation of crystal structures, one could envisage that they may change the outcome of molecular dynamics simulations since the Mg 2+ stabilization effect is much greater than that of K + (Hayatshahi et al 2017). Henceforth, it is highly probable that a decoding site modeled with one or the other ion would behave in significantly different ways and change our perception of the energetics and dynamics of the ribosomal decoding center (Lind et al 2017). Thus, it is recommended to avoid using structures that contain ions with poor stereochemistry for initiating modeling studies (Hashem and Auffinger 2009).…”
Section: The Monovalent Ion Count In Ribosomes Is Underestimatedmentioning
confidence: 99%
“…Although at first glance, such issues may not seem important for the interpretation of crystal structures, one could envisage that they may change the outcome of molecular dynamics simulations since the Mg 2+ stabilization effect is much greater than that of K + (Hayatshahi et al 2017). Henceforth, it is highly probable that a decoding site modeled with one or the other ion would behave in significantly different ways and change our perception of the energetics and dynamics of the ribosomal decoding center (Lind et al 2017). Thus, it is recommended to avoid using structures that contain ions with poor stereochemistry for initiating modeling studies (Hashem and Auffinger 2009).…”
Section: The Monovalent Ion Count In Ribosomes Is Underestimatedmentioning
confidence: 99%
“…Ribosomal scanning of mRNA is generally accepted as the predominant mechanism to locate start codons during the initiation phase of eukaryotic translation [1]. The scanning model posits that, upon cap-dependent attachment to mRNA, ribosomal small subunits (SSUs) move in a 5′ to 3′ direction (at the expense of energy; ‘powered’ motion), while the 5′UTR nucleotide sequence is being probed for codon:anticodon and local ‘nucleotide context’ interactions [1,2,3,4,5,6]. Additionally, several cap-independent [7,8,9], or eIF4E (the main cap-binding protein)-independent mechanisms have been proposed over the years to cater for translation under specific conditions and of special mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with these results, a later study by Itoh et al showed that higher serum concentrations of POPs decreased global DNA methylation in a Japanese population [183]. In contrast, a study by Lind et al on a population of 70-year-old Swedish found a relationship between high serum levels of POPs and global DNA hypermethylation [184]. Only one study examined PCB levels in human postmortem brains of patients with neurodevelopmental disorders and found that PCBs 95 was detected in 3/6 Prader-Willi syndrome postmortem brains and 5/6 postmortem brains with Dup15q.…”
Section: Epigenetic Alterations By Environmental Toxicantsmentioning
confidence: 73%